Distribution and spectrophotometric classification of basaltic asteroids. Issue 4 (3rd December 2019) - Mansour, J-A; Popescu, M; de León, J; Licandro, J
ABSTRACT: We aim to determine the distribution of basaltic asteroids (classified as V-types) based on the spectrophotometric data reported in the MOVIS-C catalogue. A total of 782 asteroids were identified. The observations with all four filters ( Y, J, H, Ks ), available for 297 of these candidates, allow a reliable comparison with the laboratory data of howardite, eucrite, and diogenite meteorites. We found that the majority of the basaltic candidates (≈95${{\ \rm per\ cent}}$ ) are located in the inner main belt, while only 29 (≈4${{\ \rm per\ cent}}$ ) and 8 (≈1${{\ \rm per\ cent}}$ ) are located in the middle (MMB) and outer main belt (OMB), respectively. A fraction of ≈33${{\ \rm per\ cent}}$ from the V-type candidates is associated with the Vesta family (with respect to AstDyS). We also identified four MMB V-type candidates belonging to (15) Eunomia family, and another four low inclination ones corresponding to (135) Hertha. We report differences between the colour indices and albedo distributions of the V-type candidates located in the inner main belt compared to those from the MMB and OMB. These results support the hypothesis of a different origin for the basaltic asteroids with a semimajor axis beyond 2.5 au. Furthermore, lithological differences are present between the vestoids and the inner low inclination basaltic asteroids. The data allow us to estimate the unbiased distribution of basaltic asteroids across the main asteroid belt. We highlight that at least 80${{\ \rm per\ cent}}$ of the ejected basaltic material from (4) Vesta is missing or is not yet detected because it is fragmented in sizes smaller than 1 km.